The knowledge and the attitude of students from the selected Lublin's universities towards the influenza vaccination - Marzena Furtak-Niczyporuk; Martyna Warchoł; Paweł Kurnik; Patrycja Gierszon (Kazimierz Wielki University, 2018)
Among all of the infectious diseases, it is influenza that affects the most people. The high infectiousness is it's characteristic, therefore people fall ill to it, regardless of age or gender. When it comes to the flu illness, the highest risk group are children and people over 65.The airways' infection caused by the flu virus is a serious health issue all around the world, causing 3-5 millions of clinical infections and 250-500 thousands deaths per year.